Manajemen Pelayanan SD Negeri 1 Kupang Teba Kecamatan Teluk Betung Utara Kota Bandar Lampung Tahun 2024/2025 - DWI NIKA RAHAYU (UNISAN JURNAL, 2025)
The management of educational services at SD Negeri 1 Kupang Teba, Teluk Betung Utara District, Lampung City, is a crucial aspect in creating an effective and efficient learning experience for students. This journal explores the implementation of management principles in improving the quality of educational services, emphasizing the importance of the roles of teachers, infrastructure, and parental involvement. Data collected from surveys and interviews indicate a significant increase in student and parental satisfaction with the educational services at this school. Analysis of educational data and statistics during the 2024/2025 academic year show that managerial efforts focused on service quality can contribute to improved student learning outcomes. Recommendations and managerial strategies are expected to be implemented to create a better learning environment.